CORRELATES OF PARTICIPATION IN MEANINGFUL ACTIVITIES AMONG PEOPLE WITH MULTIPLE SCLEROSIS - Plow, Matthew A. (J Rehabil Med, 2015)
OBJECTIVE: To explore the associations between impairments, self-management self-efficacy, self-management behaviors, and environmental factors and their role in predicting participation in meaningful activities among people with multiple sclerosis. DESIGN: Online cross-sectional survey. SUBJECTS/PATIENTS: Randomly selected individuals (n = 335) from a large multiple sclerosis patient registry. METHODS: Participation in activities that are meaningful to the individual was measured with Community Participation Indicators (CPI), the dependent variable. Independent variables included symptom severity, activities of daily living limitations, cognitive problems, stages of change for physical activity, nutritional behaviors, self-efficacy, and environmental barriers. A backwards selection regression analysis was used to compare the relative contributions of independent variables in predicting the CPI. A path analysis was conducted to explore the associations between independent variables and their direct and indirect effects on the CPI. RESULTS: The final regression model included self-management self-efficacy (β = 0.12), environmental barriers (β = −0.16), cognitive problems (β = −0.22), and stages of change for physical activity (β = 0.12). Path analysis indicated that impairments and environmental barriers might negatively influence self-management self-efficacy. Self-management self-efficacy might have indirect effects on the CPI via engagement in self-management behaviors. CONCLUSION: Future research should explore whether interventions that promote self-management self-efficacy can facilitate participation in meaningful activities.